Efficacy of Chinese herbal medicine on health-related quality of life (SF-36) in hypertensive patients: A systematic review and meta-analysis of randomized controlled trials. Issue 3 (June 2015) - Jiao, Hua-Chen; Ju, Jian-Qing; Li, Yun-Lun; Ma, Xue-Sheng; Jiang, Hai-Qiang; Zhao, Jing; Shen, Zhen-Zhen; Yang, Wen-Qing
Highlights This study systematically assessed published RCTs of Chinese Herbal Medicine improving HRQL in hypertensive patients that employ the SF-36 as an outcome measure. Meta-analysis showed that CHM appears to have beneficial effects on improvement of HRQL in hypertensive patients. Methodological quality assessment showed the actual situation of RCTs conducted in China. The majority of the included RCTs were poor methodological quality and further high quality RCTs should be carried out and reported in detail according to CONSORT.